Service Quality and Price Fairness as Determinants of Customer Loyalty: The Mediating Role of Customer Satisfaction in Service Management - Lia Rahmawati; Gunarso Wiwoho (Journal of Educational Management Research, 2026)
This study aims to examine the effects of service quality and price fairness on customer loyalty, with customer satisfaction as a mediating variable, within the context of service management. The study adopts a quantitative approach involving 100 repeat customers, selected using purposive sampling. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The results demonstrate that service quality and price fairness have positive and significant effects on customer satisfaction and customer loyalty. Customer satisfaction also shows a significant positive effect on customer loyalty and partially mediates the relationships between service quality, price fairness, and customer loyalty. These findings highlight that customer satisfaction plays a strategic role in translating service performance and pricing fairness into long-term loyalty. From a managerial and educational perspective, the study implies that organizations should strengthen service quality through continuous staff training, service-learning practices, and human capital development to enhance employees’ service competencies. Additionally, fair pricing strategies supported by transparent communication and customer-oriented education are essential in fostering trust and sustainable customer loyalty in competitive service industries.